1999
DOI: 10.1515/cclm.1999.040
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of an Intracellular Signaling Defect in Neutrophil Functional Abnormalities and Promotion of Tissue Damage in Patients with Localized Juvenile Periodontitis

Abstract: Localized juvenile periodontitis is a destructive form of periodontal inflammatory disease which has its onset at puberty. The etiopathology of the disease is still unclear but neutrophils have been suggested to play a major role both in the production and development of the disorder. About 70% of the patients with localized juvenile periodontitis exhibit neutrophil functional abnormalities, such as decreased chemotaxis and phagocytosis. Interestingly, it has been frequently reported that the same hypoactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Immune defects have also been implicated in the pathogenesis of AgP. Several investigators have shown that patients with AgP display functional defects of polymorphonuclear leukocytes (PMNs), monocytes, or both 32‐34 . These defects can impair either the chemotactic attraction of PMNs to the site of infection or their ability to phagocytose and kill microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Immune defects have also been implicated in the pathogenesis of AgP. Several investigators have shown that patients with AgP display functional defects of polymorphonuclear leukocytes (PMNs), monocytes, or both 32‐34 . These defects can impair either the chemotactic attraction of PMNs to the site of infection or their ability to phagocytose and kill microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils play a critical role in defense against periodontal pathogens, and intrinsic dysfunction or deficit of these cells predispose to the most severe forms of periodontal disease such as localized juvenile and generalized prepubertal periodontitis. The most common defects in neutrophil function are deficiencies in chemotaxis, phagocytosis, adherence and degranulation, but despite a vast literature the genetic trait(s) associated with the risk of these severe forms of disease are not fully understood (61,131,177,198,230,310). In addition, the precise molecular nature of neutrophil malfunction is known only in few cases but there is a consensus that these effects are relatively mild.…”
Section: Desensitization Of Neutrophilsmentioning
confidence: 99%
“…(5,183,262) Finally, neutrophils undergo lysis or programmed cell death (apoptosis) after the completion of their primary protective function. Abnormalities in any of these steps might result in a delayed or less ef®cient host response to bacterial challenge (6,54,160,252,288).…”
Section: Neutrophil Defects As Risk Factors For Periodontal Diseasementioning
confidence: 99%